Anti-deformation sweater and processing method thereof
By using citric acid, finishing solution and wool shrinkage agent to treat wool sweater, the problem of shrinkage of wool sweater is solved, the anti-deformation and antibacterial properties of wool are improved, and the dimensional stability and aesthetics of the sweater are maintained.
Patent Information
- Application Number
- CN202411519454.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional wool sweaters are prone to shrink after washing, which affects their beauty and service life.
The wool is treated with citric acid, finishing solution and velvet shrinkage agent. Citric acid enhances the wool's resistance to relaxation and shrinkage. Sodium polyacrylate, monoglyceride oleic acid, amino silicone oil, modified chitosan, titanium dioxide and Plant extracts improve the structural stability, antibacterial properties and feel of wool, and the wool shrinking agent reduces fiber friction, thereby reducing wool shrinking properties.
It effectively reduces the size deformation after washing, improves the drying and easy-to-care performance of wool and resists deformation, maintains the original size and shape of the fabric, and enhances antibacterial and antistatic properties.
Smart Images

Figure BDA0005107639300000091 
Figure BDA0005107639300000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of garment processing, and in particular to an anti-deformation sweater and a processing method thereof. Background Art
[0002] Sweaters are common winter clothing and are loved by consumers for their warmth and fashion. There are many types of sweaters, including animal plush fabrics, chemical fiber fabrics, cotton fabrics, linen fabrics, blended fabrics, etc. Among them, wool is the most common sweater fabric among animal plush fabrics, with good warmth retention and comfort.
[0003] Wool sweaters have high water absorption, stretch resistance, elastic recovery and durability. They can absorb and lock a lot of water while keeping a dry feeling. They are very comfortable to wear. Even after stretching, they can return to their original shape and maintain the appearance of the clothes. They have good durability. However, traditional wool sweaters become unstable in size after washing and are prone to shrinkage, which affects the appearance of the sweater and reduces its service life. Summary of the invention
[0004] In order to improve the problem of sweaters shrinking after washing, the present application provides a deformation-resistant sweater and a processing method thereof.
[0005] The present application provides a deformation-resistant sweater, which adopts the following technical solution: A deformation-resistant sweater comprises the following raw materials: wool, citric acid, finishing liquid, and milling agent; the finishing liquid comprises the following steps: sodium polyacrylate, monoglyceride of oleate, amino silicone oil, modified chitosan, titanium dioxide, plant extract, and alkyltrimethylammonium methylsulfate.
[0006] By adopting the above technical solution, in the process of preparing sweaters, citric acid, finishing liquid and shrinking agent are used to treat wool respectively. Citric acid enhances the resistance of wool to relaxation and shrinkage, helps to reduce relaxation and shrinkage after washing, and enhances the drying and easy-care performance of wool. Citric acid chemically reacts with hydroxyl (OH) and amino (NH2) in wool fibers to form esterification and amidation crosslinking, thereby improving the structural stability and deformation resistance of the fabric.
[0007] In the finishing liquid, sodium polyacrylate can chelate metal ions in water, such as calcium and magnesium. Through chelation, sodium polyacrylate can maintain the stability and effectiveness of the finishing liquid and avoid the adverse effects of metal ions on wool fibers. Oleic acid monoglyceride can activate wool fibers, improve the feel of wool fabrics, make them softer, increase whiteness and wettability, and enhance antistatic properties; amino silicone oil has excellent adsorption and compatibility, and can interact with hydroxyl, carboxyl and other groups on the surface of wool fibers, so that the siloxane main chain is directional adsorbed on the fiber surface, thereby reducing the friction coefficient between fibers, making wool fabrics softer and smoother, enhancing the tear strength and wrinkle resistance of wool fabrics, and improving the elasticity of fabrics while maintaining their original fullness.
[0008] Modified chitosan has natural antibacterial properties, which can effectively inhibit the growth of bacteria and molds. In addition, modified chitosan has a certain film-forming property, which can form a thin film on the surface of wool fibers, preventing the mutual bite between adjacent fibers and weakening the fiber directional friction effect, thereby reducing the shrinkage of wool and improving its anti-felting performance. Titanium dioxide has photocatalytic activity and can produce hydroxyl free radicals, which can effectively destroy the cell membrane and cell structure of bacteria and viruses, and improve the antibacterial and antiviral properties of wool fabrics. Plant extracts have natural antibacterial properties, which can effectively inhibit the growth of bacteria and improve the comfort and aesthetics of wool fabrics, such as improving the whiteness of fabrics and making them smoother and softer.
[0009] Alkyl trimethyl ammonium methylsulfate has good antistatic properties, which can reduce the static accumulation of wool fabrics during wearing and washing, improve wearing comfort, and the various raw materials in the finishing liquid are evenly mixed to improve the comfort and deformation resistance of wool. The shrinking agent changes the surface characteristics of wool fibers, making the surface smoother, reducing friction and entanglement between fibers, thereby reducing the possibility of shrinking; through the treatment of the shrinking agent, the dimensional stability of wool fabrics is improved, the deformation caused by hygroscopic expansion or washing is reduced, and the original size and shape of the fabric are maintained.
[0010] Preferably, the finishing liquid comprises the following steps in parts by weight: 10-12 parts of sodium polyacrylate, 2-4 parts of monoglyceride of oleic acid, 1-2 parts of amino silicone oil, 5-8 parts of modified chitosan, 0.5-1 part of titanium dioxide, 4-7 parts of plant extracts, and 2-3 parts of alkyltrimethylammonium methylsulfate.
[0011] By adopting the above technical scheme, the amount of raw materials used in the finishing liquid is further limited. Sodium polyacrylate can maintain the stability and effectiveness of the finishing liquid. Oleic acid monoglyceride can activate wool fibers, improve the whiteness and wettability of wool, and enhance the antistatic performance. Amino silicone oil enhances the tear strength and wrinkle resistance of wool fabrics. Modified chitosan effectively inhibits the growth of bacteria and mold and improves the anti-felting performance of wool. Titanium dioxide and plant extracts have bactericidal properties and effectively inhibit the growth of bacteria. Alkyl trimethyl ammonium methyl sulfate has good antistatic properties and improves wearing comfort. The raw materials are evenly mixed to jointly improve the comprehensive properties of wool.
[0012] Preferably, the preparation method of the modified chitosan comprises the following steps: (1) dispersing chitosan in an oxalic acid aqueous solution, stirring at a temperature of 60-70° C. for 10-15 min, adding dendrobium polysaccharide, and stirring evenly to obtain a mixed solution; (2) dispersing graphene in deionized water, ultrasonicating for 1-2 hours, adding sodium sulfate, stirring at a temperature of 60-65° C. for 1-2 hours, filtering, and drying to obtain pretreated graphene; (3) dispersing the pretreated graphene of step (2) in the mixed solution of step (1), adding modified attapulgite, stirring at a temperature of 70-75° C. for 1-2 h, and drying to obtain modified chitosan.
[0013] By adopting the above technical scheme, chitosan has good biocompatibility and biodegradability, and is mixed with dendrobium polysaccharides to further enhance the biocompatibility and antibacterial properties of the material, and subsequently improve the antibacterial effect and whiteness of the wool, making the wool resistant to water washing and friction, and improving its strength.
[0014] Graphene has excellent antibacterial, anti-ultraviolet, and anti-radiation functions. It can increase the tensile and friction resistance of wool and enhance the strength and durability of wool. The anions of sodium sulfate can be adsorbed on the surface of graphene and prevent the agglomeration of graphene sheets through electrostatic repulsion, making the graphene more evenly dispersed in the aqueous solution, and making the graphene more evenly attached to the wool fibers, thereby improving the strength, wear resistance and tensile resistance of the wool fibers.
[0015] Pretreated graphene is added to the mixed liquid, and graphene is dispersed in the structure of the mixed liquid. The hydrogen bonds and electrostatic interactions between chitosan and graphene enhance the structural stability of the system, and improve the mechanical properties, adsorption and antibacterial properties of the chitosan composite material. The modified attapulgite has a large specific surface area and cation exchange capacity, and has good dispersibility and adsorption. Graphene acts as a skeleton and is interconnected with chitosan molecules through hydrogen bonds, electrostatic interactions or covalent bonds to form a stable network structure. The modified attapulgite further fills the pores in the network, increases the porosity and specific surface area of the system, and the composite of graphene, chitosan and attapulgite can form a three-dimensional network structure, thereby improving its adsorption and ion exchange capacity, which is subsequently applied to the finishing liquid to improve the strength, wear resistance, tensile strength and UV protection of the wool, further improve the feel and appearance of the fabric, and reduce the shrinkage and pilling tendency of the wool.
[0016] Preferably, the mass ratio of the chitosan, graphene and modified attapulgite is 1g:60-70mg:0.1-0.3g.
[0017] By adopting the above technical scheme, the mass ratio of chitosan, graphene and modified attapulgite is further limited within a certain range, so as to improve the mechanical properties, wear resistance, adsorption and film-forming properties of chitosan. Graphene has excellent antibacterial, anti-ultraviolet and radiation protection functions. Chitosan has good biocompatibility and biodegradability. Modified attapulgite has a large specific surface area and cation exchange capacity. The composite of graphene, chitosan and attapulgite can form a three-dimensional network structure, so as to improve the strength, wear resistance, tensile strength and ultraviolet protection performance of wool and improve the structural stability of wool.
[0018] Preferably, the preparation method of the modified attapulgite comprises the following steps: dispersing the attapulgite in a sodium hydroxide solution, stirring for 15-20 minutes, washing with water, and then dispersing it in deionized water, adding nanosilver and starch, stirring at a temperature of 65-70°C for 1-2 hours, and drying to obtain modified attapulgite.
[0019] By adopting the above technical scheme, attapulgite is treated with sodium hydroxide to remove impurities in the attapulgite, thereby increasing the specific surface area and adsorption of the attapulgite. Nanosilver can be loaded in the voids of the attapulgite to improve the antibacterial effect of wool fabrics and increase the strength and stability of wool. Starch has a certain viscosity, which allows nanosilver to stably adhere to the surface of attapulgite, thereby increasing the antibacterial, viscosity and film-forming properties of the attapulgite. It is subsequently applied to modified chitosan to improve the corresponding properties of chitosan. The obtained modified attapulgite increases the surface roughness of the wool, reduces the friction between the wool, and thus reduces the tendency to pilling.
[0020] Preferably, the method for preparing the plant extract comprises the following steps: (1) crushing lotus leaves, dispersing them in an ethanol aqueous solution, adding ginger juice and acetic acid, stirring evenly, and then refluxing for extraction for 3-4 hours, the extraction number is 2-4 times, and obtaining an extract; (2) dispersing nano-silica and polyvinyl alcohol in deionized water, ultrasonicating, filtering, and drying at 110-120° C. for 1-2 hours to obtain pretreated nano-silica; (3) Dispersing the pretreated nano-silica in step (2) and the extract in step (1) in deionized water, adding hydroxymethyl cellulose, stirring at 70-75° C. for 2-3 hours, and obtaining a plant extract.
[0021] By adopting the above technical scheme, the lotus leaf extract is first extracted, and ethanol aqueous solution is used for reflux extraction. In the process of lotus leaf extraction, ginger juice and acetic acid are used as auxiliary extractants to change the structure of lotus leaf cell walls and promote the release of cell contents, thereby improving the extraction efficiency of effective ingredients in lotus leaves. Enzymes in ginger juice can decompose polysaccharides and proteins in cell walls, while the acidic environment of acetic acid helps to destroy the stability of cell walls, making it easier for effective ingredients to dissolve. Moreover, the antioxidant components in ginger juice and acetic acid can inhibit the oxidation and degradation of lotus leaf extract during the extraction process, protect the activity of effective ingredients, and gingerol in ginger juice and the acidic environment of acetic acid both help to reduce oxidation reactions and maintain the stability and biological activity of the extract.
[0022] Nano-silica is dispersed in polyvinyl alcohol, and polyvinyl alcohol is loaded on the surface of nano-silica, which improves the dispersibility of nano-silica and subsequently improves the solubility of nano-silica in other systems. Pre-treated nano-silica is dispersed in the extract, and nano-silica is dispersed in the structure of the extract to improve the mechanical properties of the extract. Nano-silica subsequently changes the surface roughness and surface energy of wool, enhances the anti-wrinkle performance of wool, enables it to maintain better elasticity in dry and wet states, and reduces the area shrinkage of wool.
[0023] Hydroxymethyl cellulose has a certain viscosity, and is subsequently used in the finishing liquid, making it easy for the plant extract to be loaded into the wool, allowing nano-silicon dioxide and the plant extract to adhere to the wool surface, thereby improving the mechanical strength and wear resistance of the wool, and effectively inhibiting the deformation and pilling problems of the wool fabric.
[0024] Preferably, the mass ratio of the lotus leaf, ginger juice and acetic acid is 1:0.2-0.3:0.3-0.4.
[0025] By adopting the above technical scheme, the mass ratio of lotus leaf, ginger juice and acetic acid is further limited within a certain range. Ginger juice improves the extraction of effective ingredients in lotus leaves, and acetic acid destroys the stability of cell walls, making the effective ingredients easier to dissolve, which helps to mix with other components later. The obtained lotus leaf extract has the effect of reducing the damage of chemical dyes to wool fibers and maintaining the natural properties and comfort of wool.
[0026] Preferably, the mass ratio of the lotus leaf, nano-silicon dioxide and hydroxymethyl cellulose is 1:0.4-0.6:0.1-0.2.
[0027] By adopting the above technical scheme, the mass ratio of lotus leaf, nano-silicon dioxide and hydroxymethyl cellulose is further limited within a certain range. Nano-silicon dioxide has good antibacterial properties, mechanical properties and wear resistance, and hydroxymethyl cellulose has a certain viscosity, so that nano-silicon dioxide and lotus leaf extract can adhere better to the surface of wool, thereby improving the mechanical properties and antibacterial properties of wool. Lotus leaf, nano-silicon dioxide and hydroxymethyl cellulose have a synergistic effect, jointly improving the corresponding properties of plant extracts, and subsequently improving the comprehensive properties of wool.
[0028] In the second aspect, the present application also provides a method for processing a deformation-resistant sweater, comprising the following steps: first dispersing the wool in a citric acid solution, soaking it for 15-20 minutes, then dispersing it in a finishing liquid, soaking it at a temperature of 80-85°C for 1.5-2 hours, drying, combing, doubling, weaving, and shrinking to obtain a deformation-resistant sweater.
[0029] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the efficiency of wool and the preparation efficiency of sweaters. The obtained sweaters have good mechanical properties and wear resistance, and can prevent deformation and pilling.
[0030] Preferably, the parameters of the double twisting are: single yarn twist is 680-700 twists, and ply spinning twist is 435-445 twists.
[0031] By adopting the above technical solution, the spinning process parameters are further limited so that the obtained yarn has better mechanical properties, which is helpful to improve the comprehensive performance of the sweater.
[0032] In summary, this application has the following beneficial effects: 1. In the present application, in the process of preparing the sweater, citric acid, finishing liquid and shrinking agent are used to treat the wool respectively. Citric acid enhances the resistance of the wool to relaxation and shrinkage, helps to reduce relaxation and shrinkage after washing, and enhances the drying and easy-care properties of the wool. Through the treatment of the shrinking agent, the dimensional stability of the wool fabric is improved, the deformation caused by moisture absorption and expansion or washing is reduced, and the original size and shape of the fabric are maintained.
[0033] 2. In the finishing liquid of the present application, the modified chitosan has natural antibacterial properties and can effectively inhibit the growth of bacteria and molds. In addition, the modified chitosan has a certain film-forming property and can form a thin film on the surface of the wool fiber to prevent the mutual bite between adjacent fibers and weaken the directional friction effect of the fibers, thereby reducing the shrinkage of the wool and improving its anti-felting performance.
[0034] 3. In the finishing liquid of the present application, the plant extract has natural antibacterial properties, which can effectively inhibit the growth of bacteria and improve the comfort and aesthetics of wool fabrics, such as increasing the whiteness of the fabric and making the fabric smoother and softer. DETAILED DESCRIPTION
[0035] The present application is further described in detail below with reference to the embodiments.
[0036] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0037] Preparation example of modified chitosan Preparation Example 1-1 The preparation method of modified chitosan comprises the following steps: (1) Dispersing 1.5 kg of chitosan in 2 L of 20% oxalic acid aqueous solution, stirring at 65° C. for 13 min, adding 0.3 kg of dendrobium polysaccharide, stirring evenly, to obtain a mixed solution; (2) dispersing graphene in 1 L of deionized water, ultrasonicating for 1.5 h, adding 0.01 kg of sodium sulfate, stirring at 65 ° C for 1.5 h, filtering, and drying to obtain pretreated graphene; (3) dispersing the pretreated graphene of step (2) in the mixed solution of step (1), adding modified attapulgite, stirring at a temperature of 75° C. for 1.5 h, and drying to obtain modified chitosan.
[0038] The mass ratio of chitosan, graphene and modified attapulgite is 1g:70mg:0.1g.
[0039] The preparation method of modified attapulgite comprises the following steps: dispersing 0.9 kg of attapulgite in 1.3 L of 15% sodium hydroxide solution by mass, stirring for 20 min, washing with water, and then dispersing in 1.5 L of deionized water, adding 0.2 kg of nano silver and 0.09 kg of starch, stirring at a temperature of 70° C. for 2 h, and drying to obtain modified attapulgite.
[0040] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), graphene is not added.
[0041] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified attapulgite is added.
[0042] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of chitosan, graphene and modified attapulgite is 1g:60mg:0.3g.
[0043] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of chitosan, graphene and modified attapulgite is 1g:50mg:0.8g.
[0044] Preparation Example 1-6 The difference from Preparation Example 1-1 is that no nanosilver is added in the preparation method of the modified attapulgite.
[0045] Preparation Example 1-7 The difference from Preparation Example 1-1 is that starch is not added in the preparation method of modified attapulgite.
[0046] Preparation example of plant extract Preparation Example 2-1 The preparation method of the plant extract comprises the following steps: (1) 1.9 kg of lotus leaves were crushed and dispersed in 3.5 L of 70% ethanol aqueous solution, ginger juice and acetic acid were added, stirred evenly, and then refluxed for 4 h and extracted 3 times to obtain an extract; (2) dispersing nano-silica and 0.3 kg of polyvinyl alcohol in 2.9 L of deionized water, ultrasonicating for 1 h, filtering, and drying at 120° C. for 1.5 h to obtain pretreated nano-silica; (3) The pretreated nano-silica obtained in step (2) and the extract obtained in step (1) were dispersed in 4.5 L of deionized water, hydroxymethyl cellulose was added, and the mixture was stirred at 75° C. for 3 h to obtain a plant extract.
[0047] The mass ratio of lotus leaf, ginger juice and acetic acid is 1:0.2:0.3.
[0048] The mass ratio of lotus leaf, nano-silicon dioxide and hydroxymethyl cellulose is 1:0.4:0.1.
[0049] Preparation Example 2-2 The difference from Preparation Example 2-1 is that ginger juice is not added.
[0050] Preparation Example 2-3 The difference from Preparation Example 2-1 is that acetic acid was not added.
[0051] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of lotus leaf, ginger juice and acetic acid is 1:0.3:0.4.
[0052] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of lotus leaf, ginger juice and acetic acid is 1:0.6:0.1.
[0053] Preparation Example 2-6 The difference from Preparation Example 2-1 is that no nano-silicon dioxide is added.
[0054] Preparation Example 2-7 The difference from Preparation Example 2-1 is that hydroxymethyl cellulose is not added.
[0055] Preparation Example 2-8 The difference from Preparation Example 2-1 is that the mass ratio of lotus leaf, nano-silicon dioxide and hydroxymethyl cellulose is 1:0.4:0.2.
[0056] Preparation Example 2-9 The difference from Preparation Example 2-1 is that the mass ratio of lotus leaf, nano-silicon dioxide and hydroxymethyl cellulose is 1:0.1:0.5. Example
[0057] Example 1 A deformation-resistant sweater comprises the following raw materials: 12kg of wool, citric acid, finishing liquid, and a milling agent; the finishing liquid comprises the following steps according to weight: 12kg of sodium polyacrylate, 4kg of oleic acid monoglyceride, 2kg of amino silicone oil, 5kg of modified chitosan, 1kg of titanium dioxide, 7kg of plant extracts, and 3kg of alkyltrimethylammonium methylsulfate.
[0058] The processing method of the anti-deformation sweater comprises the following steps: firstly dispersing the wool in 20L of citric acid solution with a mass concentration of 12%, soaking for 18 minutes, then dispersing the wool in a finishing liquid, soaking for 2 hours at a temperature of 85°C, drying, combing, doubling, weaving (flat knitting machine, weaving density is 2.3cm / 20 rows), and shrinking treatment to obtain the anti-deformation sweater.
[0059] The shrinkage treatment is as follows: immerse the wool in 19L of a solution containing a shrinkage agent for 20 minutes, the mass concentration of the shrinkage agent is 10%, and the shrinkage agent is soap oil. Twist parameters: single yarn twist is 680-700 twists, and ply spinning twist is 435-445 twists.
[0060] The modified chitosan was prepared by using Preparation Example 1-1; and the plant extract was prepared by using Preparation Example 2-1.
[0061] Example 2 A deformation-resistant sweater, which is different from Example 1 in that the finishing liquid, by weight, comprises the following steps: 10kg sodium polyacrylate, 2kg oleic acid monoglyceride, 1kg amino silicone oil, 8kg modified chitosan, 0.5kg titanium dioxide, 4kg plant extract, and 2kg alkyltrimethylammonium methylsulfate.
[0062] Example 3 A deformation-resistant sweater, which is different from Example 1 in that the modified chitosan is prepared using Preparation Example 1-2.
[0063] Example 4 A deformation-resistant sweater, which is different from Example 1 in that the modified chitosan is prepared using Preparation Examples 1-3.
[0064] Example 5 A deformation-resistant sweater, which is different from Example 1 in that the modified chitosan is prepared using Preparation Examples 1-4.
[0065] Example 6 A deformation-resistant sweater, which is different from Example 1 in that the modified chitosan is prepared using Preparation Examples 1-5.
[0066] Example 7 A deformation-resistant sweater, which is different from Example 1 in that the modified chitosan is prepared using Preparation Examples 1-6.
[0067] Example 8 A deformation-resistant sweater, which is different from Example 1 in that the modified chitosan is prepared using Preparation Examples 1-7.
[0068] Example 9 A deformation-resistant sweater, which is different from Example 1 in that the plant extract is prepared using Preparation Example 2-2.
[0069] Example 10 A deformation-resistant sweater, which is different from Example 1 in that the plant extract is prepared using Preparation Example 2-3.
[0070] Embodiment 11 A deformation-resistant sweater, which is different from Example 1 in that the plant extract is prepared using Preparation Examples 2-4.
[0071] Example 12 A deformation-resistant sweater, which is different from Example 1 in that the plant extract is prepared using Preparation Examples 2-5.
[0072] Example 13 A deformation-resistant sweater, which is different from Example 1 in that the plant extracts are prepared using Preparation Examples 2-6.
[0073] Embodiment 14 A deformation-resistant sweater, which is different from Example 1 in that the plant extract is prepared using Preparation Examples 2-7.
[0074] Embodiment 15 A deformation-resistant sweater, which is different from Example 1 in that the plant extract is prepared using Preparation Examples 2-8.
[0075] Example 16 A deformation-resistant sweater, which is different from Example 1 in that the plant extract is prepared using Preparation Examples 2-9.
[0076] Comparative Example Comparative Example 1 A deformation-resistant sweater, which is different from Example 1 in that modified chitosan is not added.
[0077] Comparative Example 2 A deformation-resistant sweater, which is different from Example 1 in that the modified chitosan is replaced by an equal amount of chitosan.
[0078] Comparative Example 3 A deformation-resistant sweater, which is different from Example 1 in that no plant extract is added.
[0079] Performance testing The wool fiber samples in the anti-deformation sweaters of Examples 1-16 and Comparative Examples 1-3 were subjected to performance tests; 1. According to the capstan method, use the Y151 fiber friction coefficient tester, clamp the two ends of the fiber with tension clamps of the same weight, and suspend it on a rotatable round roller. The roller is a fiber roller covered with fiber. Apply force under the tension clamp. When the value is equal to the static friction force of the tested fiber package on the fiber roller, the suspension body will lose balance and slide. The value is the static friction force. If the fiber is rotated counterclockwise at this time and the force is adjusted so that the suspension body regains balance, the value is the dynamic friction force.
[0080] The directional friction effect is calculated as follows: μ =(μ a -μ s ) / (μ a +μ s )×100%; In the formula, μ a is the fiber reverse friction coefficient, μ s is the fiber friction coefficient, δ μ It is the directional friction effect.
[0081] 2. Refer to the standard GBT 27629-2011, select the holding length of 180mm and the tensile speed of 100mm / min on the tensile testing machine, and take 50 wool fiber samples from each group for breaking strength test and take the average value. 3. Place each group of wool fibers in the RJ-118 high temperature and high pressure dyeing machine, adjust the wet heat treatment temperature to 90℃, treat for 35 minutes, and then test the length shrinkage and mechanical test of each group.
[0082] 4. Pilling test was carried out according to GB / T 4802.3-2008 "Determination of pilling properties of textile fabrics Part 3: Pilling box method". The specific operation is as follows: wash in a washing machine at room temperature for 60 minutes, then rub 8000 times on a YG(B)511-II rolling box pilling tester to determine the pilling degree of the sample. The smaller the level, the more serious the fabric pilling, and the larger the level, the better the anti-pilling performance. The test results are shown in Table 1.
[0083] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the anti-deformation sweaters prepared in Examples 1-2 of the present application have good mechanical properties, deformation resistance, and pilling resistance. Among them, the directional static friction effect of Example 1 is 12.34, the directional dynamic friction effect is 12.11, the breaking strength is 453cN, the length shrinkage rate is 0.53%, the fiber dry strength retention rate after wet heat treatment is 99.57%, and the pilling fastness after washing is level 5, indicating that the sweaters prepared in the present application are smoother, elastic, not easy to pilling, and can maintain the original size and shape of the sweater after washing.
[0084] In the preparation method of modified chitosan in Example 3, graphene is not added; in the preparation method of modified chitosan in Example 4, modified attapulgite is not added; in Examples 5-6, the mass ratio of chitosan, graphene and modified attapulgite is changed. As can be seen from Table 1, compared with Example 1, the static friction effect, directional dynamic friction effect and length shrinkage rate of Examples 3-4 are increased, and the breaking strength, fiber dry strength retention rate after wet heat treatment and pilling fastness after washing are decreased. The corresponding performance of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1 and 5, indicating that chitosan has good biocompatibility and biodegradability, modified attapulgite has a large specific surface area and cation exchange capacity, and the composite of graphene, chitosan and attapulgite can form a three-dimensional network structure, thereby improving the strength, wear resistance, tensile strength and ultraviolet protection of wool, and improving the structural stability of wool.
[0085] In the preparation method of modified attapulgite in Examples 7-8, nanosilver and starch are not added respectively. As can be seen from Table 1, compared with Example 1, the static friction effect, directional dynamic friction effect, and length shrinkage rate of Examples 7-8 are smaller than those of Example 4, and the breaking strength, fiber dry strength retention rate after wet heat treatment, and pilling fastness after washing are better than those of Example 4, indicating that nanosilver can be loaded in the voids of attapulgite to increase the strength and stability of wool, and starch allows nanosilver to stably adhere to the surface of attapulgite. The obtained modified attapulgite increases the surface roughness of wool, reduces friction between wool, and thus reduces the tendency to pilling.
[0086] In the preparation methods of the plant extracts of Examples 9-10, ginger juice and acetic acid are not added respectively, and the mass ratio of lotus leaf, ginger juice and acetic acid is changed in Examples 11-12. It can be seen from Table 1 that compared with Example 1, the static friction effect, directional dynamic friction effect, length shrinkage rate, breaking strength, and fiber dry strength retention rate after wet heat treatment of Examples 9-10 are all worse than those of Example 1, and the relevant performance of Example 12 is better than that of Examples 9-10, but worse than that of Examples 1 and 11, indicating that ginger juice improves the extraction of effective ingredients in lotus leaves, acetic acid destroys the stability of cell walls, and makes the effective ingredients easier to dissolve. The obtained lotus leaf extract has the effect of reducing the damage of chemical dyes to wool fibers and maintaining the natural properties and comfort of wool.
[0087] In the preparation methods of the plant extracts of Examples 13-14, nano-silicon dioxide and hydroxymethyl cellulose were not added respectively. In Examples 15-16, the mass ratio of lotus leaf, nano-silicon dioxide and hydroxymethyl cellulose was changed. As can be seen from Table 1, compared with Example 1, the static friction effect, directional dynamic friction effect, length shrinkage rate, breaking strength, and fiber dry strength retention rate after wet heat treatment of Examples 13-14 were all worse than those of Example 1. The relevant performance of Example 16 was better than that of Examples 13-14, but worse than that of Examples 1 and 15, indicating that hydroxymethyl cellulose made nano-silicon dioxide and lotus leaf extract adhere better to the wool surface, thereby improving the mechanical properties and antibacterial properties of the wool. Lotus leaf, nano-silicon dioxide and hydroxymethyl cellulose had a synergistic effect, which subsequently improved the comprehensive properties of the wool.
[0088] Comparative Examples 1 and 3 do not add modified chitosan or plant extracts, respectively. As can be seen from Table 1, compared with Example 1, the static friction effect, directional dynamic friction effect, length shrinkage, breaking strength, fiber dry strength retention after wet heat treatment, and pilling fastness after washing are all worse than those in Example 1, indicating that the modified chitosan has a certain film-forming property and can form a thin film on the surface of the wool fiber to prevent the mutual bite between adjacent fibers and weaken the directional friction effect of the fibers, thereby reducing the shrinkage of the wool and improving its anti-felting performance; the plant extract has natural antibacterial properties, effectively inhibits the growth of bacteria, improves the comfort and aesthetics of the wool fabric, and improves the whiteness of the fabric, making the fabric smoother and softer.
[0089] In Comparative Example 2, the modified chitosan is replaced by an equal amount of chitosan. It can be seen from Table 1 that, compared with Example 1, the various performance test results of Comparative Example 2 are significantly worse than those of Examples 1-2, but better than Comparative Example 1, indicating that the modified chitosan of the present application has good mechanical properties, improves the deformation resistance and pilling resistance of the sweater, and maintains the elasticity of the sweater.
[0090] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A deformation-resistant sweater, characterized in that: The invention comprises the following raw materials: wool, citric acid, finishing liquid and milling agent; the finishing liquid comprises the following steps: sodium polyacrylate, monoglyceride of oleate, amino silicone oil, modified chitosan, titanium dioxide, plant extract and alkyl trimethyl ammonium methyl sulfate.
2. The anti-deformation sweater according to claim 1, characterized in that: The finishing liquid comprises the following steps, in parts by weight: 10-12 parts of sodium polyacrylate, 2-4 parts of monoglyceride of oleic acid, 1-2 parts of amino silicone oil, 5-8 parts of modified chitosan, 0.5-1 part of titanium dioxide, 4-7 parts of plant extracts, and 2-3 parts of alkyltrimethylammonium methylsulfate.
3. The anti-deformation sweater according to claim 1, characterized in that: The preparation method of the modified chitosan comprises the following steps: (1) Dispersing chitosan in an oxalic acid aqueous solution, stirring at a temperature of 60-70°C for 10-15 minutes, adding dendrobium polysaccharide, stirring evenly to obtain a mixed solution; (2) dispersing graphene in deionized water, ultrasonicating for 1-2 hours, adding sodium sulfate, stirring at a temperature of 60-65° C. for 1-2 hours, filtering, and drying to obtain pretreated graphene; (3) Dispersing the pretreated graphene in step (2) in the mixed solution of step (1), adding modified attapulgite, stirring at a temperature of 70-75° C. for 1-2 h, and drying to obtain modified chitosan.
4. The anti-deformation sweater according to claim 3, characterized in that: The mass ratio of the chitosan, graphene and modified attapulgite is 1g:60-70mg:0.1-0.3g.
5. The anti-deformation sweater according to claim 3, characterized in that: The preparation method of the modified attapulgite comprises the following steps: dispersing the attapulgite in a sodium hydroxide solution, stirring for 15-20 minutes, washing with water, and then dispersing it in deionized water, adding nanosilver and starch, stirring at a temperature of 65-70° C. for 1-2 hours, and drying to obtain the modified attapulgite.
6. The anti-deformation sweater according to claim 1, characterized in that: The preparation method of the plant extract comprises the following steps: (1) Crush the lotus leaves, disperse them in an ethanol aqueous solution, add ginger juice and acetic acid, stir evenly, and then reflux and extract for 3-4 hours, the extraction times are 2-4 times, and an extract is obtained; (2) dispersing nano-silica and polyvinyl alcohol in deionized water, ultrasonicating, filtering, and drying at 110-120° C. for 1-2 hours to obtain pretreated nano-silica; (3) Dispersing the pretreated nano-silica obtained in step (2) and the extract obtained in step (1) in deionized water, adding hydroxymethyl cellulose, stirring at 70-75° C. for 2-3 hours, and obtaining a plant extract.
7. The anti-deformation sweater according to claim 6, characterized in that: The mass ratio of the lotus leaf, ginger juice and acetic acid is 1:0.2-0.3:0.3-0.
4.
8. The anti-deformation sweater according to claim 6, characterized in that: The mass ratio of the lotus leaf, nano silicon dioxide and hydroxymethyl cellulose is 1:0.4-0.6:0.1-0.
2.
9. The method for processing a deformation-resistant sweater according to claim 1, characterized in that: The method comprises the following steps: first dispersing the wool in a citric acid solution, soaking for 15-20 minutes, then dispersing the wool in a finishing solution, soaking for 1.5-2 hours at a temperature of 80-85 DEG C, drying, combing, doubling, weaving, and shrinking to obtain a deformation-resistant sweater.
10. The method for processing a deformation-resistant sweater according to claim 9, characterized in that: The parameters of the double twisting are as follows: the twist of single yarn is 680-700 twists, and the twist of ply spinning is 435-445 twists.